Equivalence between fixed fee and ad valorem profit royalty. (7th July 2021) - Colombo, Stefano; Ma, Siyu; Sen, Debapriya; Tauman, Yair
Abstract: For an outside innovator with a finite number of buyers of the innovation, this paper compares two licensing schemes: (i) fixed fee, in which a licensee pays a fee to the innovator and (ii) ad valorem profit royalty, in which a licensee leaves a fraction of its profit with the innovator. We show these two schemes are equivalent in that for any number of licenses the innovator puts for sale, these two schemes give the same licensing revenue. We obtain this equivalence result in a general model with minimal structure. It is then applied in a Cournot oligopoly for an outside innovator. Finally, in a Cournot duopoly it is shown that when the innovator is one of the incumbent firms rather than an outsider, the equivalence result does not hold.